2020
DOI: 10.1007/s11469-020-00294-0
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Fear of COVID-19 Scale: Its Association with Psychological Distress and Life Satisfaction in Turkey

Abstract: The world is currently experiencing a pandemic of an infectious disease called COVID-19 which has drawn global intensive attention. While global attention is largely focusing on the effects of the coronavirus on physical health, the impacts of the coronavirus on psychological health cannot be overlooked. Therefore, this study aims to adapt the Fear of COVID-19 Scale into Turkish and investigate the relationships between fear of COVID-19, psychological distress, and life satisfaction. Data were collected by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

108
726
17
37

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(888 citation statements)
references
References 17 publications
108
726
17
37
Order By: Relevance
“…Although there is a lack of similar studies of the nursing population, this relationship is in accordance with previous studies involving the general population. For instance, in a study involving 1 304 Turkish individuals, increased levels of fear of COVID-19 were strongly linked to negative emotional states including anxiety, depression and stress (Satici et al,, 2020). A study by Bakioglu et al (2020) showed a similar pattern: fear of COVID-19 had a signi cant positive relationship with anxiety, depression and stress.…”
Section: Discussionmentioning
confidence: 90%
“…Although there is a lack of similar studies of the nursing population, this relationship is in accordance with previous studies involving the general population. For instance, in a study involving 1 304 Turkish individuals, increased levels of fear of COVID-19 were strongly linked to negative emotional states including anxiety, depression and stress (Satici et al,, 2020). A study by Bakioglu et al (2020) showed a similar pattern: fear of COVID-19 had a signi cant positive relationship with anxiety, depression and stress.…”
Section: Discussionmentioning
confidence: 90%
“…Although the Turkish version also reports a single factor and has a good sample size, its authors directly carried out a con rmatory factor analysis, like others researchers did (Sakib et al, 2020;Satici et al, 2020;Tsipropoulou et al, 2020). This could explain why the Turkish version authors did not nd two factors, since they directly performed the con rmatory analysis of the original one-dimensional model (Ahorsu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This sample included more participants than those involved in the English version scale (Ahorsu et al, 2020), as well as versions in Hebrew (Tzur Bitan et al, 2020), Italian (Soraci et al, 2020), Arabic (Alyami et al, 2020), Russian (Reznik et al, 2020) and Indian (Doshi et al, 2020). However, our sample was smaller than the validationsample for the Turkish version (Satici et al, 2020), the Greek version (Tsipropoulou et al, 2020) and the Bangla version (Sakib et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The total score of the scale is obtained by summing the item scores of the respondents and higher scores on the scale demonstrate higher levels of COVID-19 fear. Turkish adaptation of the scale demonstrated satisfactory psychometric properties of the scale (Satici et al, 2020).…”
Section: Methodsmentioning
confidence: 90%